AKAP79 Orchestrates a Cyclic AMP Signalosome Adjacent to Orai1 Ca2+ Channels. Issue 5 (29th July 2021) - Kar, Pulak; Barak, Pradeep; Zerio, Anna; Lin, Yu-Ping; Parekh, Amy J; Watts, Val J; Cooper, Dermot M F; Zaccolo, Manuela; Kramer, Holger; Parekh, Anant B
Abstract: To ensure specificity of response, eukaryotic cells often restrict signalling molecules to sub-cellular regions. The Ca 2+ nanodomain is a spatially confined signal that arises near open Ca 2+ channels. Ca 2+ nanodomains near store-operated Orai1 channels stimulate the protein phosphatase calcineurin, which activates the transcription factor NFAT1, and both enzyme and target are initially attached to the plasma membrane through the scaffolding protein AKAP79. Here, we show that a cAMP signalling nexus also forms adjacent to Orai1. Protein kinase A and phosphodiesterase 4, an enzyme that rapidly breaks down cAMP, both associate with AKAP79 and realign close to Orai1 after stimulation. PCR and mass spectrometry failed to show expression of Ca 2+ -activated adenylyl cyclase 8 in HEK293 cells, whereas the enzyme was observed in neuronal cell lines. FRET and biochemical measurements of bulk cAMP and protein kinase A activity consistently failed to show an increase in adenylyl cyclase activity following even a large rise in cytosolic Ca 2+ . Furthermore, expression of AKAP79-CUTie, a cAMP FRET sensor tethered to AKAP79, did not report a rise in cAMP after stimulation, despite AKAP79 association with Orai1. Hence, HEK293 cells do not express functional active Ca 2+ -activated adenylyl cyclases including adenylyl cyclase 8. Our results show that two ancient second messengers are independently generated in nanodomains close to Orai1 Ca 2+ channels. Graphical Abstract: